Perkembangan Kesenian Dzikir Saman di Desa Wanagiri Kecamatan Saketi Kabupaten Pandeglang Tahun 1998-2017 - Andella Oktaviani; Yuni Maryuni; Arif Permana Putra (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The purpose of this study is: (1) describing the history of the formation of Dzikir Saman art in Wanagiri Village, Saketi District of Pandeglang Regency, (2) describing the development of Dzikir Saman art in Wanagiri Village, Saketi District, Pandeglang Regency in 1998-2017, (3) describing community efforts in preserving Dzikir Saman art as intangible cultural heritage in Pandeglang. The study uses historical methods consisting of heuristics, criticism, interpretation and historiography. The theoretical approaches used are cultural theory and challenge theory and response (response) from Arnold Toynbee. The study took year limits between 1998-2017. In 1998 as the beginning of the development of Dzikir Saman art in Wanagiri Village and in 2017 Dzikir Saman art in Wanagiri Village was named as Intangible Cultural Heritage by the Ministry of Education. The results of the study revealed that the art of Dzikir Saman in Wanagiri Village began from a teaching of the sammaniyah order. This sammaniyah order is a well-known teaching in Sufi science brought by Syech Samman in the 18th century. Then in the development of Dzikir Saman art in Wanagiri Village experienced the addition of function, which initially this art was only presented in religious ceremonies only on the anniversary of the Prophet Muhammad's Maulid then saw the rapid development of the times, it became a challenge for the existence of Dzikir Saman art, finally the art of Dzikir Saman was presented also in the form of performing arts, Then in its development also the art of Dzikir Saman Wanagiri Village was named as Intangible Cultural Heritage in 2017 by the Ministry of Education. Furthermore, there are preservation efforts carried out by Dzikir Saman art players, Pandeglang community and there is government carrying capacity, so that the existence of Dzikir Saman art continues to grow, these efforts include: (1) Dzikir Saman Wanagiri Village players do training every week even though this art is not staged, (2) pandeglang community always presents Dzikir Saman art in commemoration of Prophet Muhammad's Maulid, Then there is the study of Dzikir Saman art by researchers which is one form of preservation in the field of education, (3) the existence of government carrying capacity is by presenting Dzikir Saman art in a series of Pandeglang cultural festival events.